An ultrafine ruthenium nanocrystal with extremely high activity for the hydrogen evolution reaction in both acidic and alkaline media. Issue 93 (6th November 2018) - Li, Yutong; Chu, Fuqiang; Liu, Yang; Kong, Yong; Tao, Yongxin; Li, Yongxin; Qin, Yong
Abstract : An ultrafine ruthenium nanocrystal with high crystallinity features remarkable performance in the electro-catalyzed hydrogen evolution reaction in both acidic and alkaline media. Abstract : An ultrafine ruthenium nanocrystal (RuNC) was fabricated via thermal annealing tris(2, 2′-bipyridine)ruthenium dichloride with cyanuric acid. The as-obtained RuNC features a small diameter of ∼2 nm and high crystallinity. As an electrocatalyst for the hydrogen evolution reaction, the ultrafine RuNC exhibited remarkable performance in both acidic and alkaline media.